PENGARUH KONSENTRASI BIOBOOST DAN MONO KALIUM PHOSPAT TERHADAP PRODUKSI KACANG MERAH VARIETAS INERIE DI DATARAN RENDAH - Yosefina Lewar; Ali Hasan; Stormy Vertygo (Jurnal Penelitian Pertanian Terapan, 2024)
The research objective  to examine the best concentration of BioBoost and MKP, as well as their interaction, in enhancing the production of kidney beans of the Inerie variety in lowlands. The study was designed using a Factorial Randomized Complete Block Design with treatments including BioBoost concentrations (10 ml/l, 15 ml/l, 20 ml/l, 25 ml/l) and MKP concentrations (5 g/l, 10 g/l, 15 g/l). The data were analyzed for variance and tested with Honestly Significant Difference at 5%. The research results indicate that 1) BioBoost at 25 ml/l resulted in the lowest number of empty pods (1.67 pods), the highest number of seeds per plant (44.61 grains), the heaviest seed weight per plant (15.80 g), and the heaviest weight of 100 seeds (36.29 g), 2) MKP at 15 g/l resulted in the highest number of seeds per plant (40.14 grains), the heaviest seed weight per plant (14.30 g), and the heaviest weight of 100 seeds (34.61 g), and 3) the interaction between BioBoost concentration at 25 ml/l and MKP at 5 g/l  was the best for the highest number of filled pods (15.89 pods) and the lowest number of wrinkled seeds (0.75 grains).